Specificity of Salt Marsh Diazotrophs for Vegetation Zones and Plant Hosts: Results from a North American marsh - Davis, Debra A.; Lovell, Charles R. (Frontiers in Microbiology, 2012)
Salt marshes located on the east coast of temperate North America are highly productive, typically nitrogen-limited, and support diverse assemblages of free-living nitrogen fixing (diazotrophic) bacteria. This article reviews and analyzes data from North Inlet estuary (SC, USA), addressing diazotroph assemblage structure and the influence of plant host and environmental conditions on the assemblage. The North Inlet estuary is a salt marsh ecosystem in which anthropogenic influences are minimal and the distributions of diazotrophs are governed by the natural biota and dynamics of the system. Denaturing gradient gel electrophoresis fingerprinting and phylogenetic analyses of recovered sequences demonstrated that the distributions of some diazotrophs reflect plant host specificity and that diazotroph assemblages distributed across marsh gradients are also heavily influenced by edaphic conditions. Broadly distributed diazotrophs that are capable of maintaining populations under all environmental conditions spanning such gradients are also present in these assemblages. Statistical analyses indicate that the structures of diazotroph assemblages in different vegetation zones are significantly (p < 0.01) different. New data presented here demonstrate the heterogeneity of salt marsh rhizosphere microenvironments, and corroborate previous findings from different plant hosts growing at several locations within this estuary. The data from these collected works support the hypothesis that the biogeography of microorganisms is non-random and these biogeographic patterns are predictable.